1995
DOI: 10.1515/hfsg.1995.49.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Wood and Synthetic Polymers

Abstract: The properties of wood composites consisting of low density polyethylene (LDPE) and wood flour (WF) were studied. In an attempt to improve the interfacial adhesion between hydrophobic LDPE matrix and the hydrophilic WF filler, a styrene-butadiene-styrene (SBS) copolymer was added as a compatibilizer. The interaction between LDPE and wood was investigated for PE/WF-and PE/WF/SBScomposites. The experimental measurements were conducted by conventional mechanical testing and Scanning Electron Microscopy (SEM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
4
29
0
1
Order By: Relevance
“…The SBS was found to locate at the interface between the wood and LDPE matrix having a cylindrical morphology and an interface thickness of approximately 0.1 mm. 13 It is expected that the morphology of composite systems would be similar regardless of the material used (SBS or SEBS-MA).…”
Section: Compatibilizermentioning
confidence: 99%
See 4 more Smart Citations
“…The SBS was found to locate at the interface between the wood and LDPE matrix having a cylindrical morphology and an interface thickness of approximately 0.1 mm. 13 It is expected that the morphology of composite systems would be similar regardless of the material used (SBS or SEBS-MA).…”
Section: Compatibilizermentioning
confidence: 99%
“…After that, the samples were stained with OsO 4 WF-SBS system. 13 The SBS compatibilizer was stained with OsO 4 to distinguish it from the LDPE vapor for about 2 h in order to give good contrast for the unsaturated part of the EB-MA blocks in matrix. As a result of the study, the SBS was found to locate at the interface between the PE the copolymers.…”
Section: Morphology Of Compositesmentioning
confidence: 99%
See 3 more Smart Citations